Morphological Variation in Clinically Erupted Mesiodens: A Case Series - Tripathi, Roshila; Vaidya, Subhani; Dikshit, Parajeeta; Malla, Manisha; Limbu, Senchhema (Journal of Nepalese Association of Pediatric Dentistry, 2023)
Mesiodens are the most common supernumerary teeth, commonly located in anterior maxilla, placed labially, palatally or in between the maxillary central incisors with a higher prevalence in males. This case series depicts clinically visible mesiodens in young children with morphological variables (eumorphic or dysmorphic), which were managed by extraction under local anesthesia.